El Dia de la foto - Buckless, Andrea; Goodnow, Patti (New York : Scholastic Inc., 2003)
The only student to stick her tongue out in the class picture has to figure out how to fix this terrible mistake.
"Cartwheel books."
Grades kindergarten-grade 2"--cover.
Accelerated Reader AR
Keywords: Photographs -- Fiction; Spanish language materials